Timbulnya Keyakinan Hakim dalam Hukum Pembuktian Perkara Pidana di Peradilan Indonesia - Gulo, Nimerodi; Cornelius Dikae Zolohefona Gulo (LPPM Universitas Ekasakti Padang, 2024)
Legal proof in a criminal case is the process of convincing a judge of the truth of an event that is the basis of a claim or defence in a case. Legal proof has various aspects, methods, and systems that are governed by the rules of the law in force. Legal proof also relates to the concepts of justice, certainty, and validity of the law. The purpose of legal proof is to a fair, true, and in accordance with the facts and law. Law proof faces a variety of challenges and problems, such as the limitation of the means of proof, the difficulty of testing the validity and authenticity of evidence, and the influence of non-law factors on proof. Therefore, legal proof requires improved quality, professionalism, and integrity of the perpetrators, whether judges, prosecutors, lawyers, or witnesses. The methods used are the Legislative approach, the Case approach, and the Conceptual approach. By looking at whether the law of our events is still relevant to the existing case, then how to solve the problem with the emerging views and doctrines in criminal law. The legal proof in criminal cases is also very close to the emergence of judges' beliefs, so the judge is obliged to apply the theory relevant to the conditions that exist at the time of the decision of a case. Thus, theory used must follow the case and the development of the doctrine in the law of criminal cases.